Role of histamine release in hypertonic saline induced bronchoconstriction. - O'Hickey, S P (1989)
In a study designed to determine the protective effect of the specific histamine H1 antagonist terfenadine on hypertonic saline induced bronchoconstriction, 10 asthmatic subjects underwent hypertonic saline challenge (3.6%) after premedication with placebo or terfenadine (120 mg) 12 and two hours before the challenge. Hypertonic saline was administered in a dose dependent manner and the response determined as the dose of hypertonic saline that induced a 20% fall in FEV1 (PD20 FEV1). FEV1 was on average 11% greater with terfenadine than with placebo given before the challenge with hypertonic saline. PD20 FEV1 was attenuated by a mean of 2.5 fold after terfenadine (geometric mean PD20 FEV1 was 22 litres after placebo and 56 l after terfenadine). There was substantial intersubject variation in the inhibitory effect of terfenadine on hypertonic saline induced bronchoconstriction: the ratio of the PD20 hypertonic saline after terfenadine to that after placebo ranged from 0.9 to 10.0. Terfenadine inhibited histamine induced bronchoconstriction in the eight subjects in whom it was tested, by 13 to 160 fold compared with placebo in four subjects and by greater than 2 to greater than 9 fold in the four who showed no response to the highest dose of histamine given (16 mg/ml). These results suggest that histamine release has a role in hypertonic saline induced bronchoconstriction in some individuals; other mediators or mechanisms may have a more prominent role in others.